Physics in Sport Education: Insights from a decade of bibliometric analysis (JTIKOR (Jurnal Terapan Ilmu Keolahragaan), 2024)
This study aims to analyze the trends in scientific publications related to the application of physics in sports education over the past decade using a bibliometric approach. Data was collected from the Scopus database using the keywords "TITLE-ABS-KEY(Physics AND Sport AND Education)" within the 2015–2024 range, resulting in 83 documents. The extracted data, in CSV and RIS formats, was analyzed using VOSviewer 1.6.20 and Microsoft Excel 365 to conduct co-authorship and co-occurrence analyses. The results indicate that research in this field focuses on biomechanics, coaching strategies, and the technological integration in sports learning and training, with a significant increase in the use of digital monitoring systems. It can be concluded that physics education in sports continues to evolve through technological innovations, yet there are still gaps in its application to enhance the effectiveness of learning and coaching. Future research should adopt a multidisciplinary approach to enhance the integration of physics-based technology in sports education and training.